Evaluating the Effectiveness of Management Practices in Accounting Information Systems (AIS) within Nepali Commercial Banks - Subedi, Purushottam; Sharma, Ravi (A Bi-annual South Asian Journal of Research & Innovation, 2024)
This paper investigates the relation between management practices and Accounting Information System (AIS) effectiveness within Nepali banking sector. It has brought the practices that are significant transformation due to regulatory reforms, technological advancements, and keen competition. As commercial banks expand and modernize, the effectiveness of their Accounting Information Systems (AIS) has become crucial for maintaining financial accuracy, operational efficiency, and regulatory compliance. Despite this, study on the influence of management practices on AIS effectiveness in Nepali banks remains limited. It has the gap by exploring how various management practices such as top management support, IT governance, human resource management, and risk management affect the effectiveness of AIS in Nepali commercial banks. Utilizing the Technology-Organization-Environment (TOE) framework and the Unified Theory of Acceptance and Use of Technology (UTAUT), this research assesses the factors that contribute to the successful implementation and utilization of AIS. Through a mixed-method approach, including quantitative analysis of financial data and qualitative interviews with key stakeholders, the study provides a comprehensive evaluation of AIS effectiveness in this context. The findings highlight the critical role of strong IT governance, ongoing staff training, and top management support in enhancing AIS effectiveness. Additionally, the study identifies key challenges, such as inadequate infrastructure and resistance to change, which hinder optimal AIS utilization. By offering evidence-based insights and practical recommendations, this research contributes to the development of robust strategies for improving AIS management practices in Nepali commercial banks, ultimately enhancing their operational performance and competitiveness.